Ethical and psychological factors of social activity of modern young people - Elena E. Bocharova (Saratov State University, 2021)
The purpose of the study presented in the article is an empirical study of the relationship between characteristics of moral selfdetermination and various forms of social activity of young people. The study involves students (N = 236): high school students (n = 118) and university students (n = 118) of Saratov and Saratov Oblast (Russia) aged from 17 to 19 years. We use the following techniques as methodological tools: a questionnaire aimed at registering various forms of social activity and the degree of its manifestation (R. M. Shamionov, I. V. Arendachuk, E. E. Bocharova and others) and the "Moral self-determination of an individual" technique (A. E. Vorobyova, A. B. Kupreychenko) to record the characteristics of moral self-determination. The hypothesis of the study is an assumption regarding presence of multidirectional relationships between the measures of manifestation of the moral self-determination parameters and self-assessments of various forms of social activity. Recognition of the importance of morality and ethics is a positive predictor of altruistic and educational and developmental forms of activity of schoolchildren and a negative predictor in the case of actualization of the socio-economic activity of university students. We have recorded the tendency of positive dynamics in the manifestation frequency of relationships between the parameters of moral self-determination and forms of social activity: from the minimum number among schoolchildren to its increase among university students. The materials presented can be implemented in the practice of advisory services of educational institutions and in the organization of socially useful activities of young people.